The direct and catalytic Pyrolysis of Rice Straw - Razi Ahmad (School of Environmental Engineering, 2010)
A study of the catalytic pyrolysis on rice straw was carried out in a fixed-bed reactor. The work objectives were to determine the influences of pyrolysis parameters i.e pyrolysis temperature, heating rate and holding time on distribution of product yield.